Resistance of wild African ungulates to foraging by red-billed oxpeckers (Buphagus erythrorhynchus): Evidence that this behaviour modulates a potentially parasitic interaction - Bishop, A.L.; Bishop, Richard P. (Wiley, 2014)
Field observations of the interactions between red-billed oxpeckers (Buphagus erythrorhynchus) and wild ungulates in Nakuru National Park, Kenya, revealed that specific hosts frequently attempted to manipulate oxpecker foraging. This involved a repertoire of behaviour collectively referred to as resistance behaviour, and often resulted in the oxpeckers either changing their position on the host's body or departing. Cape buffalo (Syncerus caffer), the most frequently used host, performed little resistance behaviour. Waterbuck (Kobus ellipsiprymnus) were also popular oxpecker hosts, but frequently exhibited vigorous resistance behaviour. Impala (Aepyceros melampus), the third most widely used host species, also utilized resistance behaviours, but allowed a greater proportion of oxpeckers to forage without disturbance. The suite of resistance behaviours employed by waterbuck, impala and also the consequences for oxpecker foraging, differed significantly. Our data suggest that the oxpecker-ungulate interactions in the field are more complex than previously realized with resistance behaviour regularly employed by selected mammalian host species.